Hierarchical porous carbons with layer-by-layer motif architectures from confined soft-template self-assembly in layered materials - Jie Wang (Nature Portfolio, 2017)
2D nanomaterials are promising capacitive energy storage materials, but their tendency to restack hinders electrolyte transport. Here, Yamauchi and colleagues introduce 2D ordered mesoporous carbons in between MXene layers, and metal removal affords all-carbon porous 2D–2D heterostructures in which restacking is prevented.